Perceptions of Climate Change among Small-Scale Farmers in Kasambandola, Katete District, Zambia - Elizabeth Soko; Brivery Siamabele; Rockiner Kenneth Simoonga; Aurick Mubita (Archives of Current Research International, 2025)
Climate change poses a significant global development challenge, particularly for communities that rely on rain fed agriculture for their livelihoods, such as small-scale farmers. This study investigated small-scale farmers’ perceptions of climate change manifestations in the Kasambandola community of Katete District, in Eastern Province of Zambia. It employed a convergent mixed methods research design (QUAL+quant) where quantitative data played a complementary and supportive role to the qualitative data. The data was collected using semi-structured questionnaires, key informant interviews and focus group discussions. The sample comprised of 91 small scale farmers and 6 key informants. Qualitative data were analyzed thematically, while quantitative data was analyzed using Excel. The findings highlighted farmers’ perceptions of climate change as characterized by unpredictable rainfall patterns, shorter rainy seasons, and extreme weather events. These perceptions were corroborated by meteorological data, which showed significant variations in rainfall patterns over time. Respondents reported that these climatic changes severely impacted agricultural productivity, with maize yields—once ranging from 15–20 oxcarts per farmer—declining to just 2–8 oxcarts. In response, farmers implemented a mix of traditional practices, such as making heaped lines and expanding their farms through deforestation, alongside modern techniques like ripping, the Gamphani system, improved crop varieties, and crop diversification. While these adaptation strategies have shown promise, the study recommended the need for small-scale farmers to fully embrace sustainable agricultural practices to enhance resilience and mitigate the adverse effects of climate change.